Audit of caesarean deliveries in a tertiary care rural hospital of Bangalore, Karnataka, India - Sarvotham, Ananya; Fathima, A. Arshia; Indrani, Chaitanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Due to the rise in caesarean section rates Robsons classification system was adopted by WHO as a global standard to asses and audit the caesarean section rates within different hospitals, to reduce the caesarean section rates and the associated complications and also improve patient care along with it. The aim of the present study is to audit the number of caesarean deliveries in the hospital. Objective were to audit the caesarean deliveries in the institution using Robsons classification system as the starting point to find the contributing factors responsible for the caesarean section rates. Methods: This retrospective hospital-based study was conducted at MVJMC and RH. The study included all pregnant patients undergoing caesarean section during the period of one year from March 2023 to February 2024. All the data was entered into Microsoft excel, sheet, which was then classified according to Robson’s classification system. Results: In our study we noted that the highest percent of caesarean deliveries was noted among multigravida which contributed about 66.5 of the total caesarean deliveries and according to classification 35% of the caesarean deliveries was noted in group 3 with multiparous women of more than 37 weeks in spontaneous labour. Conclusions: Globally accepted Robsons classification should be used for regular audits among hospitals to curb the caesarean section and its associated maternal and perinatal complications in order to improve patient care.